Evaluation of Sacroiliac Wedge Rotation to Increase Acetabular Ventroversion - Conzemius, M. G.; Aper, R. L.; Brown, M. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
Treatment of canine hip dysplasia (CHD) via triple pelvic osteotomy (TPO) is widely accepted as the treatment that best preserves the existing hip joint. TPO, however, has several important disadvantages. In an effort to avoid some of the difficulties associated with TPO an alternative method of creating acetabular ventroversion (AW) was sought. The purpose of this study was to explore the effects of placement of a wedge in the sacroiliac (SI) joint on A W and to compare this to the effect of TPO on A W . On one hemipelvis a 30° pelvic osteotomy plate was used for TPO. The contralateral hemipelvis had a 28° SI wedge inserted into the SI joint. Pre- and postsurgical radiographs of each pelvis were taken and the angular measurements were recorded. On average, the 28° SI wedge resulted in 20.9° of A W, the 30° canine pelvic osteotomy plate resulted in 24.9° A W . Significant differences were not found (p >0.05) between the two techniques. Sacroiliac wedge rotation effectively creates A W and has several theoretical advantages when compared to TPO. The in vivo effects of sacroiliac wedge rotation should be studied in order to evaluate the clinical effect of the technique.Sacroiliac wedge rotation was tested as an alternative method to increase the angle of acetabular ventroversion. This technique effectively rotated the acetabulum and has several theoretical advantages when compared to triple pelvic osteotomy.
Keywords: Acetabular canine